HIV pre-exposure prophylaxis use during periods of unprotected sex among female sex workers in Tanga city, Tanzania: a control arm analysis of the pragmatic quasi-experimental trial - Wigilya P. Mikomangwa; Wigilya P. Mikomangwa; Wigilya P. Mikomangwa; Kåre Moen; Elia J. Mmbaga; Elia J. Mmbaga; Emmy Metta; Stephen M. Kibusi; Melkizedeck T. Leshabari; Appolinary A. R. Kamuhabwa; Gideon Kwesigabo (Frontiers Media S.A., 2024)
BackgroundPre-exposure prophylaxis (PrEP) prevention-effective adherence is of critical importance but challenging particularly among key populations where periods of high HIV risk are frequent. We assessed the use of PrEP with reference to periods of unprotected sex among female sex workers in the city of Tanga.MethodsThis was part of the pragmatic quasi-experimental trial for HIV PrEP rollout in Tanzania involving a control cohort of 313 female sex workers aged ≥18 years recruited by respondent-driven sampling and followed for 12 months. PrEP use and periods of condomless or unprotected sex were assessed at the 6th and 12th month of follow-up. Prevention-effective adherence was defined as PrEP use of ≥2 pills/week and ≥6 pills/week for anal and vaginal condomless sex. Multivariable modified Poisson regression was conducted to determine factors influencing PrEP use (≥2 pills/week).ResultsOverall, 59.2 and 45.9% of participants had unprotected anal and vaginal sex with a client, respectively. The prevention-effective adherence for anal sex ranged from 8.0% (months 6) to 10.0% (months 12) while that of vaginal sex was from 10.1% (month 6) to 3.8% (month 12). Participants who lived with friends were 25.5 times more likely to use ≥2 PrEP doses per week than those who lived alone (aPR = 25.5; 95%CI: 2.55-255.42, p = 0.006). Compared to self-reporting poor health status, self-reporting good health status significantly increased the use of ≥2 PrEP doses per week (aPR = 17.4; 95%CI: 3.01-101.02, p = 0.001). Refusing condomless sex with a steady partner increased the likelihood of using ≥2 PrEP doses per week than accepting condomless sex with a steady partner (aPR = 11.2; 95%CI: 1.55-80.48, p = 0.017). The prevalence of using ≥2 PrEP doses per week was less among participants accepting condomless sex at high pay than those who refused (aPR = 0.1; 95%CI: 0.03-0.26, p = 0.000).ConclusionUse of PrEP during periods of unprotected sex was rare among female sex workers. Living with friends, self-reporting good health status, and refusing condomless sex with steady partners were associated with increased use of ≥2 PrEP doses per week. However, accepting condomless sex for increased payment was associated with reduced use of ≥2 PrEP doses per week. This calls for an in-depth study to understand the perspectives and circumstances shaping poor adherence during periods of unprotected sex among female sex workers.